Analysis of concrete properties with partial sand replacement by recycled plastic and its cost–benefit evaluation - Alam, Pervez; Mazhar, Mohd. Aamir; Verma, Mohit; Farooq, Umar; Khan, Afzal Husain (Frontiers in Materials, 2025)
The rising demand for sustainable and environmentally friendly construction materials has encouraged the exploration of alternatives to natural sand in concrete production. This study evaluates the feasibility of partially replacing fine aggregates with recycled polyvinyl chloride (PVC) and polyethylene terephthalate (PET) plastics in concrete. Concrete mixes of grades M15, M20, and M25 were prepared with plastic aggregate replacement levels of 0%, 5%, 10%, 15%, and 20%. The PET and PVC waste materials were melted, crushed, and incorporated into concrete mixtures, and their effects on workability and compressive strength were systematically examined. The results showed that in M15 concrete, workability remained adequate at 5% and 15% PET replacement; however, its compressive strength gradually decreased with increasing plastic content, showing a maximum reduction of 46.51% at 20% replacement. In contrast, both M20 and M25 mixes maintained acceptable workability across all replacement levels, and their compressive strengths consistently surpassed the standard minimum requirements of 20 N/mm2 and 25 N/mm2, respectively. Comparisons between PET and PVC replacements revealed slight reductions in workability (approximately 5%–8%) and compressive strength (approximately 5%–15%) as the substitution level increased. Although several studies have explored alternatives to natural sand, limited research has systematically examined the combined effects of PET and PVC plastics on the workability and strength of different concrete grades. This study addresses that gap by evaluating the performance of M15, M20, and M25 concretes with varying levels of PET and PVC replacements, identifying the feasible substitution range that maintains acceptable mechanical and workability properties. The findings demonstrate that up to 20% replacement is suitable for M20 and M25 grades without significant loss of strength, thereby contributing to sustainable construction practices through effective plastic waste utilization and conservation of natural resources.